Endospore-forming soil bacteria - Logan, Niall A.; De Vos, Paul.; SpringerLink (Online service). (Heidelberg New York Springer, 2011)
Aerobic endospore-forming bacteria are found in soils of all kinds, ranging from acid to alkaline, hot to cold, and fertile to desert. It is well known that endospores confer special properties upon their owners and play dominant parts in their life cycles and dispersal, and much has been written about the spores, genetics, and economic importance of these organisms. Much has also been written about soil ecology, but there is a relative dearth of literature that brings together different aspects of the behaviour and characters of endospore-formers with their contributions to soil ecosystems. This Soil Biology volume fills that gap. Following chapters that describe the current classification of these organisms, that review methods for their detection and for studying their life cycles in soils, and that examine their dispersal, other chapters show that they are active and dynamic members of soil floras that interact widely with other soil inhabitants, with roles in nitrogen fixation, denitrification, and soil remediation.
1. Developments in the taxonomy of aerobic, endospore-forming bacteria / Niall A. Logan and Gillian Halket -- 2. Diversity of endospore-forming bacteria in soil: characterization and driving mechanisms / Ines Mandic-Mulec and James I. Prosser -- 3. Studying the bacterial diversity of the soil by culture-independent approaches / Paul De Vos -- 4. Exploring diversity of cultivable aerobick endospore-forming bacteria: from pasteurization to procedures without heat-shock selection / O. Berge, P. Mavingui, and T. Heulin -- 5. Life cycle and gene exchange / Xiaomin Hu and Jacques Mahillon -- 6. Studying the life cycle of aerobic endospore-forming bacteria in soil / Volker S Brözel, Yun Luo, and Sebastien Vilain -- 7. Dispersal of aerobic endospore-forming bacteria from soil and agricultural activities to food and feed / Marc Heyndrickx -- 8. Biological control of phytopathogenic fungi by aerobic endospore-formers / Alejandro Pérez-García, Diego Romero, Houda Zeriouh, and Antonio de Vicente -- 9. Pasteurai penetrans and its parasitic interaction with plant parasitic nematodes / Alistair H. Bishop -- 10. Aerobic endospore-forming bacteria and soil invertebrates / Helmut König -- 11. Bacillus thuringiensis diversity in soil and phylloplane / Michio Ohba -- 12. Brevibacillus, arbuscular mycoorhizae and remediation of metal toxicity in agricultural soils / Juan Manuel Ruiz-Lozano and Rosario Azcón -- 13. Beobacillus activities in soil and oil contamination remediation / Ibrahim M. Banat and Roger Marchant -- 14. Studying denitrification by aerobic endospore-forming bacteria in soil / Ines Verbaendert and Paul De Vos -- 15. Paenibacillus, nitrogen fixation and soil fertility / Lucy Seldin -- 16. Halophilic and haloalkalilphilic, aerobic endospore-forming bacteria in soil / M. Carmen Márquez, Cristina, Sánchez-Porro, and Antonio ventosa.
Electronic reproduction.
Keywords: Soil microbiology; Sporeforming bacteria; Electronic books